Environmental safety of genetically engineered crops - Grumet, Rebecca (Michigan State University Press, 2011)
Since the mid-1990s, when the technology was first introduced, the cultivation of genetically engineered (GE) crops has grown exponentially. In the U.S. alone, adoption rates for transgenic cotton, corn, and soybeans are between 70-90%. Across the globe, 14 million farmers grow GE crops in more than twenty countries. Yet many countries are discussing and debating the use and adoption of GE technology because of concerns about their impact on the environment and human health. Now, in this comprehensive handbook, a team of international experts present the scientific basis for GE crops,